Status, Distribution, and Threats of Red Panda (Ailurus fulgens Cuvier, 1825) in Nepal - Aliza Subedi; Prasamsa Shrestha; Prakash Ojha (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
One of the world's most appealing species is the Red Panda (Ailurus fulgens). Red pandas were earlier extensively distributed around Eurasia, but they're still only found in Nepal, Bhutan, India, Myanmar, and China. The pandas had a high fatality rate and minimal reproduction (usually one cub/female/year). The red panda is the only species of its kind in the world that is still living in the inaccessible Tibetan cultural sites including Langtang and other Himalayan slopes, rendering its protection vital to the preservation of Nepal's natural assets and the world's biodiversity. The purpose of this article is to describe the status, distribution, and threats of red pandas in Nepal which could be a turning point for carrying out additional studies and red panda conservation. Various articles, books, and reports that were published between 1979 and 2021 were evaluated for this purpose using Google Scholar, Research Gate, etc. For the review, we pursued 59 pieces of paper. Despite being extremely vital from preservation, technical, and socioeconomic basis, this species has seen a drop in its wild population. Globally there are less than 10,000 individuals left and in Nepal, there are about 317-552 individuals. Natural hazards also pose a risk to the habitat of exotic species like the Red Panda, in addition to human expansion, infrastructure development, scenic spots, habitat alteration, and modes of interaction.